Marketing research in the developing countries : a handbook - Kracmar, John Z. (New York : Praeger Publishers, 1971)
The object in writing this book has been to help bridge the gulf in the literature by contributing an affirmative opinion to the general discussion of the obstacles and possibilities of marketing research in the developing areas.
Includes bibliographical references: p. 317-322.
II 18/01/2019
Loans
Keywords: Marketing research